Effect of Tungsten on the Pitting and Crevice Corrosion Resistance of Type 25Cr Super Duplex Stainless Steels - Iannuzzi, Mariano; Haugan, E.; Næss, M.; Torres Rodriguez, C.; Johnsen, R. (NACE International, 2016)
The oil and gas industry regularly uses Type 25Cr super duplex stainless steels (SDSS) for components exposed to seawater and hydrocarbon environments in topside facilities, downhole, and subsea equipment. Much debate still exists concerning the effect of tungsten on pitting and crevice corrosion resistance, particularly in standardization committees. Whereas some researchers claim that tungsten has a strong synergistic effect with molybdenum when added above a certain threshold value, others argue that tungsten additions at the expense of molybdenum could lower corrosion resistance. The objective of this investigation was to examine the effect of tungsten on localized corrosion of two super duplex stainless steels: a low-W (modified UNS S32750) and a high-W (UNS S39274) grade. Both crevice-free and creviced samples were studied. Tests were conducted in 3.5 wt% NaCl or natural seawater with temperatures ranging from 20°C to 95°C. Various independent methodologies including cyclic potentiodynamic polarization, electrochemical critical pitting temperature testing per ASTM G150, and long-term open-circuit potential exposure in natural seawater were used. Results showed that, in the solution annealed condition, tungsten additions to super duplex stainless steels had a marked positive effect on pitting and crevice corrosion resistance, increasing critical crevice temperatures by as much as 30°C. These findings suggested that tungsten-containing SDSS had a corrosion resistance on par with super austenitic stainless steel grades containing 6 wt% molybdenum. A new parametric definition of the pitting resistant equivalent is proposed to reflect the alloy’s localized corrosion resistance and to support standardization efforts in the materials oil and gas community.